Usual interstitial pneumonia in ANCA-associated vasculitis: A poor prognostic factor. Issue 106 (January 2020) - Maillet, Thibault; Goletto, Tiphaine; Beltramo, Guillaume; Dupuy, Henry; Jouneau, Stéphane; Borie, Raphael; Crestani, Bruno; Cottin, Vincent; Blockmans, Daniel; Lazaro, Estibaliz; Naccache, Jean-Marc; Pugnet, Grégory; et al.
Abstract: Background: Progressive fibrosing interstitial lung disease (ILD) is rarely associated with antineutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV). This study focused on the outcomes of ILD patients with associated AAV (AAV–ILD). Methods: AAV–ILD (cases: microscopic polyangiitis (MPA) or granulomatosis with polyangiitis (GPA) with ILD) were compared to AAV patients without ILD (controls). ILD was defined as a usual interstitial pneumonia (UIP) or non-specific interstitial pneumonia (NSIP) pattern. Two controls were matched to each case for age (>or ≤65 years), ANCA status (PR3-or MPO-positive) and creatininemia (≥or <150 μmol/L). Results: Sixty-two cases (89% MPO-ANCA+) were included. Median age at AAV diagnosis was 66 years. ILD (63% UIP), was diagnosed before (52%) or simultaneously (39%) with AAV. Cases versus 124 controls less frequently had systemic vasculitis symptoms. One-, 3- and 5-year overall survival rates, respectively, were: 96.7%, 80% and 66% for cases versus 93.5%, 89.6% and 83.8% for controls (p = 0.008). Multivariate analyses retained age >65 years (hazard ratio (HR) 4.54; p < 0.001), alveolar haemorrhage (HR 2.25; p = 0.019) and UIP (HR 2.73; p = 0.002), but not immunosuppressant use, as factors independently associated with shorter survival. Conclusion: For AAV–ILD patients, only UIP was associated with poorer prognosis. Immunosuppressants did not improve the AAV–ILD prognosis. But in analogy to idiopathic pulmonary fibrosis, anti-fibrosing agents might be useful and should be assessed in AAV–ILD patients with a UIP pattern. Highlights: Progressive fibrosing interstitial lung disease is a rare comorbidity of MPO-vasculitis. This condition is associated with shorter survival when it has a CT-scan UIP pattern. Immunosuppressants did not improve the prognosis of these patients. Our results support the evaluation of anti-fibrotic drugs in this condition.